Life Table of the Green Lacewing Apertochrysa sp. (Neuroptera:Chrysopidae) Reared on Rice Moth Corcyra cephalonica(Lepidoptera: Pyralidae) - Alasady, Mohammed Abid Ali; Omar, Dzolkhifli; Ibrahim, Yusof; Ibrahim, Rohani (2010)
The survivorship from egg to adult emergence and fertility of Apertochrysa sp. fed on Corcyra cephalonica were studied in laboratory and population parameters of Apertochrysa sp. were used for construction of life table under ideal condition in laboratory free from natural enemies. The highest mortality occurred in eggs (44.3%) followed by mortality (15.4%) in 2nd instar larva and in pupal stage (11.4%). The sex ratio (proportion of female to male) was 1:1.4. The maximum life span of female was 38 days. The highest number of eggs produced per female was 6.33 at seventh day of oviposition. The gross reproductive rate (GRR) was 19.48 females per female per generation. The net reproductive rate (Ro) was 2.28 females per female per generation. Mean generation time (T) was 40.6 days, while the intrinsic rate of natural increase (r) was 0.02 female per female per day. The finite rate of increase (λ) was 1.02 females per female per day. The population double time (DT) was within 14.8 day.